Smart waste sorter chute / Nur Syifaa Hashim and Hasni Suryani Mat Hasan - Hashim, Nur Syifaa; Mat Hasan, Hasni Suryani (2023)
High-rise buildings nowadays are a symbol of a country's rapid growth. The rapidly growing construction sector in Malaysia has produced numerous types of waste products that caused a negative impact on the environment and increased the amount of waste in landfills. The considerable volume of garbage produced during the construction of high-rise buildings makes waste management a crucial component of the project. Due to the lack of a systematic approach to managing construction waste, reducing waste as the building construction industry grew into what it is now became a significant environmental issue. The objectives of this innovation project are to identify the suitable method of waste management for high-rise building construction, propose sustainable element of waste chute in high-rise building construction, and determine the marketability of proposing sustainable waste chute in high- rise building construction in order to achieve the aim of this study which is, to develop an innovative product to manage waste in construction industry as sustainable waste management. The technology requires an expertise in order to provide the high-quality performance. Sustainable future may be brought by technological advancements, which help to protect the environment and conserve resources by reducing waste generation and improving resource efficiency.